c - Dobson, James C., 1936- (Puerto Rico : c, 1981)
Speaks to adolescents about such topics as drug abuse, sex, family conflict, friendship, love, and conformity.
Translation of Preparing for adolescence.
Keywords: Adolescence -- Juvenile literature; Conduct of life; Christian life